Aftermath of Apixaban: Atypical Anticoagulation Aftereffect - Bhesh Karki; Louis Costanzo; Sameer Joshi; Aleksey Fiksman (Case Reports in Rheumatology)
An elderly man with prostate cancer and a deep vein thrombosis (DVT) of the lower extremity diagnosed 12 days ago on apixaban presented with a new-onset palpable rash on both of his legs. Extensive laboratory workup was largely unremarkable, except for multiple skin punch biopsies revealing deposition of immunoglobulin A (IgA) in the superficial blood vessels with infiltration of leukocytes, concerning for a small vessel vasculitis. Given the temporal association along with the negative workup, the rash was attributed to apixaban, and the anticoagulation regimen was switched to dabigatran. At a 2-week follow-up visit, the patient was asymptomatic and tolerating dabigatran without any adverse events.